3D printing and nir fluorescence imaging techniques for the fabrication of implants - Suh, Yong Joon; Lim, Tae Hyeon; Choi, Hak Soo; Kim, Moon Suk; Lee, Sang Jin; Kim, Soon Hee; Park, Chan Hum (Materials, 2020)
Three-dimensional (3D) printing technology holds great potential to fabricate complex constructs in the field of regenerative medicine. Researchers in the surgical fields have used 3D printing techniques and their associated biomaterials for education, training, consultation, organ transplantation, plastic surgery, surgical planning, dentures, and more. In addition, the universal utilization of 3D printing techniques enables researchers to exploit different types of hardware and software in, for example, the surgical fields. To realize the 3D-printed structures to implant them in the body and tissue regeneration, it is important to understand 3D printing technology and its enabling technologies. This paper concisely reviews 3D printing techniques in terms of hardware, software, and materials with a focus on surgery. In addition, it reviews bioprinting technology and a non-invasive monitoring method using near-infrared (NIR) fluorescence, with special attention to the 3D-bioprinted tissue constructs. NIR fluorescence imaging applied to 3D printing technology can play a significant role in monitoring the therapeutic efficacy of 3D structures for clinical implants. Consequently, these techniques can provide individually customized products and improve the treatment outcome of surgeries.
Keywords: Customized products; Enabling technologies; Hardware and software; Near-infrared fluorescence; Nir fluorescence imaging; Non-invasive monitoring; Therapeutic efficacy; Three-dimensional (3D) printing; 3D printing; Bioprinting; Fabrication; Implants; Near-infrared fluorescence imaging